Novo surto de leishmaniose tegumentar americana em área de treinamento militar na Zona da Mata norte do Estado de Pernambuco New outbreak of American tegumentary leishmaniasis in a military training center in the Zona da Mata region, in the north of the State of Pernambuco - Maria Sandra Andrade; Maria Edileuza Felinto Brito; Salomão Thomaz da Silva; Edna Ishikawa; Silvia Maria Santos Carvalho; Sinval Pinto Brandão-Filho (Revista da Sociedade Brasileira de Medicina Tropical, 2009)
Relata-se novo surto de LTA em militares com 71 casos confirmados pelos critérios clínico, epidemiológico e laboratorial. Obteve-se o isolamento de sete amostras, identificadas como Leishmania (Viannia) braziliensis. A ocorrência de surtos nesta região confirma o caráter endêmico, cuja magnitude parece estar relacionada a não adoção de medidas de proteção individual. A new outbreak of American tegumentary leishmaniasis among military personnel is reported, with 71 cases confirmed by means of clinical, epidemiological and laboratory criteria. Seven samples were isolated and were identified as Leishmania (Viannia) braziliensis. The occurrence of outbreaks in this region confirms the endemic nature of this disease, and the magnitude of the occurrence seems to be related to non-adoption of individual protection measures.